Production and purification of recombinant proteins VP2 and VP3 of the Alongshan virus of the Jingmenvirus group and evaluation of their immunochemical properties - Ekaterina V. Bondarenko; Elena A. Ermolaeva; Ivan S. Kholodilov; Aleksander G. Litov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. Alongshan virus is a representative of the unclassified group of Jingmenviruses (Flaviviridae), which is detected in Ixodes persulcatus, Ixodes ricinus ticks and various mosquito species in Russia, China, Finland and France. Unlike traditional orthoflaviviruses, the Alongshan virus genome is represented by 4 positive-sense RNA segments. The first and third segments of the genome encode proteins homologous to proteins of the replicative machinery of orthoflaviviruses, the remaining segments encode putative structural proteins that have no known homologues: segment 2 — VP1a (envelope protein), VP1b and NuORF; segment 4 — VP2 (capsid) and VP3 (membrane). Human cases of Alongshan virus-associated disease have been described.